Volatile and odoriferous compounds changes during frozen concentrated orange juice processing - Mastello, Raíssa Bittar [UNESP]; Janzantti, Natália Soares [UNESP]; Monteiro, Magali [UNESP] (Elsevier, 2015)
Sixty-two volatile compounds were identified in orange juice from frozen concentrated orange juice (FCOJ) processing steps using HSSPME-GC-MS in combination with GC-OSME. Twenty-four compounds were perceived by OSME in the juice from the extraction step, twenty-five from the finishing step, nineteen from the 1st stage of evaporator step, nine from the concentration step and fourteen from the blending step. Ethyl butanoate, d-limonene, nonanal, ethyl octanoate and decanal showed major odoriferous importance for the juice from the extraction step. They were also considered to be of major odoriferous importance in the finishing step, apart from nonanal and ethyl octanoate. d-Limonene showed the highest odoriferous intensity in all the steps and it was the only major compound in the 1st stage of evaporator, concentration and blending steps. The majority of compounds showed a decrease in odour intensity during the processing. Principal component analysis showed that syrup, fruity, green, lavender, citrus and green leaf descriptors were reduced during the processing, from the extraction and finishing steps up to the 1st stage of evaporator step, while stink bug increased. Gas and green leaf descriptors were more important to the aroma of the juice from the 1st stage of evaporator, concentration and blending steps, and eucalyptus and plastic to the juice from the extraction and finishing steps. Ten volatile compounds were quantified by HS-SPME-GC-MS. Ethyl butanoate concentration was higher in the finishing step, being strongly reduced in the 1st stage of evaporator step, and β-pinene, myrcene and longifolene were higher in the extraction step. 1-Octanol, linalool, α-terpineol, β-citronellol, perillaldehyde and decanal were higher in the finishing step. All of them showed a decrease in concentration from the extraction and finishing step up to the end of the FCOJ processing, affecting the final product aroma quality.
Keywords: FCOJ processing steps; GC-olfactometry; HS-SPME-GC-MS; Orange juice; Volatile compounds